Review on Biosynthesis of β-Nicotinamide Mononucleotide and Its Derivatives - WANG Zhaoying, GUO Xinhao, HUANG Xinhe, CHEN Zhuoyan, LIU Yueqi, LI Juan, CHEN Ning, FAN Xiaoguang (Shipin Kexue)
β-Nicotinamide mononucleotide (NMN) is present in all organisms and has attracted widespread attention as a nutritional supplement and pharmaceutical product for the treatment of various diseases, such as Alzheimer’s disease, cancer, aging, and vascular dysfunction. Chemical synthesis is the major method for producing NMN, but it faces challenges such as complex synthesis routes, harsh reaction conditions, difficulties in chiral separation of products, and the use of organic solvents, resulting in high product price and limited applications. In contrast, biosynthesis, with its significant advantages of non-toxicity, mild processing conditions, high substrate specificity, strong product selectivity, and high conversion efficiency, has gradually become an ideal alternative for NMN production. NMN is biosynthesized mainly from niacinamide, nicotinamide riboside, niacin, or glucose through different metabolic pathways, and the key enzymes involved include nicotinamide phosphoribosyltransferase, nicotinamide riboside kinase, and NMN synthase. This article focuses on the latest progress in the enzymatic and microbial production of NMN, including the selection and modification of key enzymes, the design of enzymatic cascade reaction, the immobilization of enzymes, the construction of cell factories, and optimization strategies for the fermentation process. In addition, the biosynthesis technologies for NMN derivatives nicotinamide riboside (NR) and nicotinamide adenine dinucleotide (NAD+) are reviewed. These studies will provide references for the development of low-cost, high-efficiency methods for the production of NMN and its derivatives.